2016
DOI: 10.3141/2544-08
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Express Train Choice of Metro Passengers from Smart Card Data

Abstract: This paper addresses the problem of predicting the express local train choices of metro passengers. The model was built and tested on the preferences observed from smart card data. The revealed preference data, because of intensiveness, can also accurately capture the marginal effects of the core attributes, in-vehicle time and wait time, on the express train choices by metro passengers. To be specific, the marginal disutility of a path decreases in in-vehicle time and increases in wait time. Accordingly, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Studies on urban or suburban express railway services like GTX have found that the properties of express railways such as mobility (3) and punctuality (4) have a great influence on the mode choice process. In addition, the possibility of using the suburban express rail is also increased through reducing the out-vehicle time (5) by improving accessibility or strengthening the linkage of modes and enhancing convenience by reducing congestion (6,7) in the vehicle and similar results are obtained from studies on Gyeong-in Line and Line 9 (8)(9)(10) in the metropolitan area of Seoul based on transportation card data. Although these studies could provide meaningful insights about properties of express rail or suburban rail services in mode choice process, diverse travel contexts which might affect the utility of using the express railway services tend to be ignored.…”
supporting
confidence: 58%
“…Studies on urban or suburban express railway services like GTX have found that the properties of express railways such as mobility (3) and punctuality (4) have a great influence on the mode choice process. In addition, the possibility of using the suburban express rail is also increased through reducing the out-vehicle time (5) by improving accessibility or strengthening the linkage of modes and enhancing convenience by reducing congestion (6,7) in the vehicle and similar results are obtained from studies on Gyeong-in Line and Line 9 (8)(9)(10) in the metropolitan area of Seoul based on transportation card data. Although these studies could provide meaningful insights about properties of express rail or suburban rail services in mode choice process, diverse travel contexts which might affect the utility of using the express railway services tend to be ignored.…”
supporting
confidence: 58%
“…Lee et al distinguished the preference between the local train boarded group and the express train boarded using the Gaussian mixture model with smart card data (6). Kim et al also employed smart card data to develop an express train choice model, and the results of the train choice model indicated that passengers preferred the express train over the local (7).…”
mentioning
confidence: 99%
“…Kim et al [19] deduced whether the route chosen by passengers of Subway Line 9 comprised express, regular, or mixed commutes by using the boarding and alighting information at the first and last stations of the line and investigated changes in the commuters' choices between the express and local trains after the extension of the line. Kim et al [20] focused on the Gyeongin Line to establish both linear and non-linear utility functions, with in-vehicle time and waiting time set as explanatory variables, and assessed the goodness-of-fit of the model based on the degree of explanation provided by the coefficient.…”
Section: Literature Reviewmentioning
confidence: 99%